A Four-Point Screening Method for Assessing Molecular Mechanism of Action (MMOA) Identifies Tideglusib as a Time-Dependent Inhibitor of Trypanosoma brucei GSK3β. - Zachary T Swinney; Brad A Haubrich; Shuangluo Xia; Chakk Ramesha; Stephen R Gomez; Paul Guyett; Kojo Mensa-Wilmot; David C Swinney (Public Library of Science (PLoS), 2016)
New therapeutics are needed for neglected tropical diseases including Human African trypanosomiasis (HAT), a progressive and fatal disease caused by the protozoan parasites Trypanosoma brucei gambiense and T. b. rhodesiense. There is a need for simple, efficient, cost effective methods to identify new molecules with unique molecular mechanisms of action (MMOAs). The mechanistic features of a binding mode, such as competition with endogenous substrates and time-dependence can affect the observed inhibitory IC50, and differentiate molecules and their therapeutic usefulness. Simple screening methods to determine time-dependence and competition can be used to differentiate compounds with different MMOAs in order to identify new therapeutic opportunities.In this work we report a four point screening methodology to evaluate the time-dependence and competition for inhibition of GSK3β protein kinase isolated from T. brucei. Using this method, we identified tideglusib as a time-dependent inhibitor whose mechanism of action is time-dependent, ATP competitive upon initial binding, which transitions to ATP non-competitive with time. The enzyme activity was not recovered following 100-fold dilution of the buffer consistent with an irreversible mechanism of action. This is in contrast to the T. brucei GSK3β inhibitor GW8510, whose inhibition was competitive with ATP, not time-dependent at all measured time points and reversible in dilution experiments. The activity of tideglusib against T. brucei parasites was confirmed by inhibition of parasite proliferation (GI50 of 2.3 μM).Altogether this work demonstrates a straightforward method for determining molecular mechanisms of action and its application for mechanistic differentiation of two potent TbGSK3β inhibitors. The four point MMOA method identified tideglusib as a mechanistically differentiated TbGSK3β inhibitor. Tideglusib was shown to inhibit parasite growth in this work, and has been reported to be well tolerated in one year of dosing in human clinical studies. Consequently, further supportive studies on the potential therapeutic usefulness of tideglusib for HAT are justified.